Effect of Entrepreneurship Education on Poverty Alleviation and Entrepreneurial Intention among Graduates of the Centre for Entrepreneurship and Innovation (Cei) University of Ibadan - Ogunrinade, S.A (Covenant Journal of Entrepreneurship, 2024)
Entrepreneurship education is one of the essential keys to human capital development, economic growth, and national development. This study, therefore, examined the effect of entrepreneurship education on poverty alleviation and entrepreneurial intention among graduates of the Centre for Entrepreneurship and Innovation (CEI), University of Ibadan. A descriptive survey research study design was adopted after reviewing relevant literature. The research instrument used for this work is a structured questionnaire. The items were constructed to elicit responses from the respondents. The study population is the students who have undergone entrepreneurship education at the University of Ibadan. Quantitative data was collected from a purposive sample of 200 respondents using a pre-tested semi-structured questionnaire. Data collected were analysed using Chi-square and presented in tables. From the findings, the statistical result of the first hypothesis shows a statistically positive significant effect of entrepreneurship education on entrepreneurship intention at (sig = 0.000 < 0.05). The second hypothesis's statistical result shows a statistically significant effect of entrepreneurial education on poverty eradication in society at (sig = 0.000 < 0.05). The study concludes that profitable and sustainable business creation is possible through entrepreneurship education, which offers students essential skills, motivation, and awareness. The study also recommended that academic institutions invest massively in training students to develop a culture of value creation to solve professional and socio-economic issues. Keywords:, . , ,